Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1002/polb.10570
|View full text |Cite
|
Sign up to set email alerts
|

Solidlike transition of melt‐intercalated biodegradable polymer/clay nanocomposites

Abstract: Synthetic biodegradable aliphatic polyester (BAP) intercalated into organoclay was prepared by melt compounding, and its solidlike characteristics were investigated via several rheological test modes: steady shear rotation, oscillation, and creep testing. Structural investigations with X‐ray diffraction and transmission electron spectroscopy were also performed for a better understanding of the characteristic rheological behaviors. The creep, recovery, and stress modulus exhibited a solidlike transition of BAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…From these results, we conjugate the existence of a critical concentration at which a remarkable increase in the modulus is achieved. Similar results were reported for BAP/OMMT nanocomposites prepared via melt intercalation, showing a significant increase in storage modulus and elastic recovery at a clay content of 3 wt.-% [18]. Furthermore, a plot of G′ versus G″ for different temperatures can be used as an effective method to elucidate structural changes [19], analogous to Cole-Cole plots in dielectric spectroscopy [20].…”
Section: Resultssupporting
confidence: 59%
“…From these results, we conjugate the existence of a critical concentration at which a remarkable increase in the modulus is achieved. Similar results were reported for BAP/OMMT nanocomposites prepared via melt intercalation, showing a significant increase in storage modulus and elastic recovery at a clay content of 3 wt.-% [18]. Furthermore, a plot of G′ versus G″ for different temperatures can be used as an effective method to elucidate structural changes [19], analogous to Cole-Cole plots in dielectric spectroscopy [20].…”
Section: Resultssupporting
confidence: 59%
“…As widely reported for composite materials [10,[12][13][14][15][16][17][22][23][24][27][28][29], a better nanoclay dispersion yields an increase in interfacial area, allowing for optimal mechanical stress transfer between the filler and the matrix and, therefore, an enhancement in mechanical behaviour. In this regard, as discussed in previous works [15,16], the disappearance of the rubbery plateau region in the 24 h-bitumen/C20A/MDI composite has been attributed to the effects of MDI-related reactions under low shear processing, which, in fact, may promote the agglomeration/re-aggregation of C20A tactoids/platelets through interactions between hydroxyl groups located on the edges of the clay platelets [10,12,[15][16][17].…”
Section: Linear Viscoelastic Behaviourmentioning
confidence: 99%
“…In general, the observed rheological behaviour hints at the development of a complex, clay-based micro-and nano-structured continuum that reinforces the system structure and derives from the intercalation/exfoliation of clay tactoids in the bituminous matrix [14][15][16]23,24].…”
Section: Linear Viscoelastic Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…PCNs show significant improvement in properties when compared with neat polymer and polymers containing micron-sized fillers. Several studies have reported that PCNs show improvement in mechanical properties (Okada et al 1990;Giannelis 1996;Chen et al 2002;Maity et al 2002;Lim et al 2003;Ma et al 2003;Park et al 2003;Pramanik et al 2003;Pramoda et al 2003), a decrease in gas permeability (Yano et al 1993;Messersmith & Giannelis 1995;Bharadwaj 2001;Xu et al 2001) and flammability (Gilman et al 1997(Gilman et al , 2000Gilman 1999) and also affect the biodegradability of biodegradable polymers (Ray et al 2002). There has also been considerable interest in modelling and in the simulation and development of new theories for PCNs.…”
Section: Introductionmentioning
confidence: 99%